2020
DOI: 10.3390/nu12041138
|View full text |Cite
|
Sign up to set email alerts
|

The Gastroprotective Effect of Small Molecule Oligopeptides Isolated from Walnut (Juglans regia L.) against Ethanol-Induced Gastric Mucosal Injury in Rats

Abstract: The study investigated the protective effect of walnut oligopeptides (WOPs) against ethanol-induced gastric injury using Sprague-Dawley (SD) rats. Rats were randomly divided into seven groups based on body weight (10/group), normal group, ethanol group, whey protein group (220 mg/kg body weight), omeprazole group (20 mg/kg body weight), and three WOPs groups (220, 440, 880 mg/kg body weight). After 30 days of treatment with WOPs, rats were given 5 mL/kg absolute ethanol by gavage to induce gastric mucosal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…The anti-ulcer and gastroprotective effects of drugs, natural phytochemicals, and herbs have been commonly assessed using an ethanol-induced gastric lesion rodent model ( Simoes et al, 2019 ). Alcohol intubation causes depletion of the gastric wall mucosal barrier via ROS and cytokine upregulation, which lead to oxidative-stress-induced damage ( Abdel-Salam et al, 2001 ; Liu et al, 2020 ). In the present investigation, ethanol intubation caused severe oxidative-stress-induced damage in rats with ethanol-induced ulcers; this was consistent with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-ulcer and gastroprotective effects of drugs, natural phytochemicals, and herbs have been commonly assessed using an ethanol-induced gastric lesion rodent model ( Simoes et al, 2019 ). Alcohol intubation causes depletion of the gastric wall mucosal barrier via ROS and cytokine upregulation, which lead to oxidative-stress-induced damage ( Abdel-Salam et al, 2001 ; Liu et al, 2020 ). In the present investigation, ethanol intubation caused severe oxidative-stress-induced damage in rats with ethanol-induced ulcers; this was consistent with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. (2020) indicated that walnut oligopeptides have protective effects against ethanol‐induced gastric mucosal injury in vivo through anti‐inflammatory, antioxidation, and antiapoptosis mechanisms. Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies acknowledged positive effect of RUT in peritoneal resident macrophages (Li et al, 2019), monocytes (Liu et al, 2016), osteoclast (Fukuma et al, 2018), HepG2 cells (Jin et al, 2017;Surbala et al, 2020) and Hepa-1c1c7 cells (Lee et al, 2012). Meanwhile, RUT has shown versatile beneficial effects on several experimental models, such as colitis (Zhang et al, 2020), atherosclerosis (Luo et al, 2020, cerebral ischemia-reperfusion (Han et al, 2019), hypertension (Ma et al, 2019), Acute kidney injury (Liu et al, 2020a;Liu et al, 2020b), type 2 diabetic (Surbala et al, 2020), Alzheimer's disease (Ahmad et al, 2020;Huang et al, 2020) and so on. Notably, RUT exerted definite anti-inflammatory, anti-oxidation and anti-apoptosis effects in several experimental pathology with the signaling of NF-κB, Nrf2/HO-1, Bcl-2/Bax pathways (Jin et al, 2017;Li et al, 2019a;Li et al, 2019b;Han et al, 2019).…”
Section: Introductionmentioning
confidence: 99%